Tokoh Bambang Ekalaya dan Moralitas Pendidikan - AGUS PRASETYA (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2008)
Bambang Ekalaya and The Education Morality. Si Bambang Ekajaya is a story that is produced from theeducation morality condition that is growing in society at this time, and than commuted be a play manuscript story,it means that the appraise these are justifi cation and contraction. It can also be said as criticism what are looked andheard as a respond. The creation of Si Bambang Ekajaya used inter-textual theory, which inter-textual theory is tofi nd some aspects which have already exist in the works before, which appears more in the text. From some aspects,inter-textual principle can also be connected to literature work reception.